Advancedness in second language Spanish : definitions, challenges, and possibilities - Menke, Mandy R.; Malovrh, Paul A. (Issues in Hispanic and Lusophone linguistics, 2021)
"This book analyzes the construct of advanced proficiency in second language learning by bringing together empirical research from numerous linguistic domains and methodological traditions. Focusing on the dynamic nature of language use, the volume explores diverse manifestations of high-level second language Spanish, including performance on standardized proficiency assessments, acquisition of late-acquired linguistic structures, sophisticated language use in context, and individual differences. Chapters relate empirical findings to current definitions of advancedness, challenging scholars and practitioners to re-consider existing conceptualizations, and propose possible directions for future research and teaching with second language speakers of Spanish. By addressing larger issues in the field of second language learning, the volume is a valuable reference for language teachers, scholars, professionals and students with an interest in second language acquisition generally, and second language Spanish, more specifically"--